THE IMPACT OF SLEEP ON MENTAL HEALTH: A COMPREHENSIVE REVIEW ACROSS THE LIFESPAN - Patrycja Jagura; Julia Groszewska; Michał Romaniuk; Agata Rapior; Kinga Lubomska; Daria Makowska-Woszczyk; Agata Mytych; Jan Romaniuk; Łukasz Nosek; Marta Dziedziak (International Journal of Innovative Technologies in Social Science, 2026)
Background: Sleep plays a crucial role in mental health throughout life. Disrupted, insufficient, or irregular sleep has been linked to adverse emotional, cognitive, and psychological outcomes from childhood through older adulthood. Early identification and intervention may mitigate long-term consequences of sleep disturbances.Methods: A narrative review of peer-reviewed literature published between 2015 and 2025 was conducted using PubMed and Google Scholar. The review focused on sleep duration, sleep quality, circadian disruption, and their associations with mental health outcomes across different age groups.Results: Across all life stages, poor sleep was consistently linked to higher risks of depression, anxiety, cognitive impairments, and subclinical psychotic symptoms. Vulnerability was particularly pronounced in adolescents, young adults, and older adults. The relationship between sleep and mental health appeared to be bidirectional, with sleep disturbances both contributing to and resulting from psychiatric symptoms. Interventions focused on improving sleep, such as sleep hygiene programs and Cognitive Behavioral Therapy for Insomnia, were shown to enhance sleep quality and alleviate a range of mental health difficulties.Conclusion: Sleep is a modifiable and clinically significant factor for mental health. Integrating sleep assessment and interventions into routine mental health care, along with public education and population-level strategies, may substantially enhance mental well-being across the lifespan.